2016
DOI: 10.1186/s12967-016-1097-0
|View full text |Cite
|
Sign up to set email alerts
|

Directed differentiation of human iPSC into insulin producing cells is improved by induced expression of PDX1 and NKX6.1 factors in IPC progenitors

Abstract: BackgroundInduced pluripotent stem cells (iPSC) possess an enormous potential as both, scientific and therapeutic tools. Their application in the regenerative medicine provides new treatment opportunities for numerous diseases, including type 1 diabetes. In this work we aimed to derive insulin producing cells (IPC) from iPS cells established in defined conditions.MethodsWe optimized iPSC generation protocol and created pluripotent cell lines with stably integrated PDX1 and NKX6.1 transgenes under the transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 58 publications
(58 reference statements)
1
28
0
Order By: Relevance
“…This finding suggests the presence of a common progenitor of neurons and insulin-positive cells during in vitro differentiation (Soria, 2001 ). Moreover, the IPC derived from induced pluripotent stem cells could be enhanced by overexpression of Pdx1 and Nkx6.1 factors (Walczak et al, 2016 ). In the present study, the expression of Nkx6.1 was detected starting at DE formation stage and then increased until the later stages of differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggests the presence of a common progenitor of neurons and insulin-positive cells during in vitro differentiation (Soria, 2001 ). Moreover, the IPC derived from induced pluripotent stem cells could be enhanced by overexpression of Pdx1 and Nkx6.1 factors (Walczak et al, 2016 ). In the present study, the expression of Nkx6.1 was detected starting at DE formation stage and then increased until the later stages of differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Two components of the oriP and Epstein-Barr nuclear antigen-1 (EBNA-1) are also used widely in episomal plasmids [32][33][34][35][36][37][38] . Yu et al reported that human iPSCs that are completely free of plasmids and transgene sequences could be derived from fibroblasts by a single transfection with oriP/ EBNA-1-based episomal plasmids [39][40][41][42] .…”
Section: Non-integrative Methods Of Ipsc Productionmentioning
confidence: 99%
“…The human cells reported to have been successfully reprogrammed into EiPSCs include fibroblasts, epithelial cells, keratinocytes, mononuclear cells from adult peripheral blood, cord blood cells, amniotic fluid stem cells, mesenchymal stromal cells, lymphoblasts, lamina propria progenitor cells from oral mucosa, and urothelial cells obtained from urine. A summary of these reported human EiPSC sources is shown in Table 1 8,20,21,[32][33][34][35][36][37][38][39][40][41][42][43][47][48][49][50][51][52]55,56,58, . The variety of cell lineages that can be reprogrammed by episomal techniques demonstrates the versatility of this technique, which has been used in many laboratories around the world.…”
Section: Human Eipsc Sourcesmentioning
confidence: 99%
“…This protocol involves the addition of various differentiation-inducing factors to the culture media at each differentiation stage, because of which the expression of transcription factors that are speci c to that particular pancreatic developmental stage is induced. Small molecules are also being widely used as differentiation-inducing factors, and IPCs generated using small molecules have shown robust function in vivo and in vitro [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%